2012
DOI: 10.1155/2012/124068
|View full text |Cite
|
Sign up to set email alerts
|

Natural Breeding Places for Phlebotomine Sand Flies (Diptera: Psychodidae) in a Semiarid Region of Bahia State, Brazil

Abstract: Few microhabitats have been previously identified as natural breeding places for phlebotomine sand flies so far, and little is known about the influence of climate variables in their density. The present study was conducted in a dry region with a semiarid climate, where visceral leishmaniasis occurs in humans and dogs. The occurrence of breeding places in specific microhabitats was investigated in soil samples collected from five houses, which were also the location used for sampling of adults. All the microha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
2
22
0
2
Order By: Relevance
“…Many studies have shown that sand fly densities are influenced by climatic conditions especially high temperatures and humidity [5, 22, 44, 45]. Consistent with those observations, those factors also influenced the occurrence of sand flies, mainly in the summer months (January and February) when temperatures and precipitation increased.…”
Section: Discussionsupporting
confidence: 67%
“…Many studies have shown that sand fly densities are influenced by climatic conditions especially high temperatures and humidity [5, 22, 44, 45]. Consistent with those observations, those factors also influenced the occurrence of sand flies, mainly in the summer months (January and February) when temperatures and precipitation increased.…”
Section: Discussionsupporting
confidence: 67%
“…The lack of correlation between the number of adult sand flies collected in CDC traps and the number of immature stages in soil samples, or adults in emergence traps, is not uncommon [26], [50], [51]. This could be due to an accumulation of multiple generations of flies in the CDC trap, in addition to the fact that adults are attracted to the host from an area considerable larger than the emergence microhabitats that are sampled.…”
Section: Resultsmentioning
confidence: 99%
“…Rock soil type was the most important predictor of ZVL occurrence in the current study. Rock soil was found to be a good resting place for sandflies, and different studies showed an abundance of sandflies in this soil type in the new and old World foci (Asimeng, ; Ferro et al, ; Ovallos et al, ; Sangiorgi et al, ).…”
Section: Discussionmentioning
confidence: 99%